2005
DOI: 10.1088/0953-8984/17/14/012
|View full text |Cite
|
Sign up to set email alerts
|

The shape of barchan dunes

Abstract: Abstract. Barchans are crescent-shaped sand dunes forming in aride regions with unidirectional wind and limited sand supply. We report analytical and numerical results for dune shapes under different environmental conditions as obtained from the so-called 'minimal model' of aeolian sand dunes. The profiles of longitudinal vertical slices (i.e. along the wind direction) are analyzed as a function of wind speed and sand supply. Shape transitions can be induced by changes of mass, wind speed and sand supply. With… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
5
35
1
Order By: Relevance
“…In their experiment, they found dunes 800 times smaller than the aeolian dunes, since ρ fluid of water is 10 3 kg/m 3 . As observed recently, there are other physical variables besides ℓ drag which appear relevant to explain the scale of dunes [15]. Barchans are also found on Mars, where the atmospheric density is 100 times smaller than on earth.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In their experiment, they found dunes 800 times smaller than the aeolian dunes, since ρ fluid of water is 10 3 kg/m 3 . As observed recently, there are other physical variables besides ℓ drag which appear relevant to explain the scale of dunes [15]. Barchans are also found on Mars, where the atmospheric density is 100 times smaller than on earth.…”
Section: Introductionmentioning
confidence: 60%
“…7a how different a barchan dune of width 180 m appears with different values of shear velocity and sand influx q in /q s from 1 to 50%. Kroy et al (2005) [15] have already shown that the aspect ratio H/L increases with u * . Furthermore, there is an interesting feature which we can only see with three-dimensional calculations.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, because of the low fluid density on Mars, saltation there takes a much greater distance to reach steady state than on Earth. In fact, the "drag length" required to accelerate particles to the fluid speed is approximately two orders of magnitude greater on Mars than on Earth [Kroy et al, 2005]. Since wind tunnels require ∼10 meters to reach steady-state saltation for Earth conditions [Shao and Raupach, 1992], studies using similar wind tunnels for Mars conditions cannot measure steady-state conditions, and will thus underestimate the mass flux [Anderson and Haff, 1991;Shao and Raupach, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…The Martian higher entrainment rate, which is a result of the larger splash events on Mars, shortens the length of flux saturation and reduces the scale of dunes that is obtained if only the Martian larger saltation length is considered [48,53];…”
Section: Discussionmentioning
confidence: 99%